Sharia Business Practice in the Span of Retail Business Franchises - Noor Maymunah (Jurnal Ekonomi, 2026)
In this era of globalization, franchise expansion is one of the main strategies in the growth of the retail industry. In a business framework guided by Islamic values, the importance of business ethics is increasing. This article explores the role of Islamic Business Ethics in the context of the retail industry's franchise expansion, with a focus on the economic cycle and Islamic business practices. Through a literature review, this article outlines how Islamic business ethical values can guide franchise expansion measures, manage risk in fluctuating economic cycles, and implement sharia business methods that adhere to Islamic values. This study reviews the impact of Islamic business ethics principles in strengthening the foundations of sustainability and long-term success for the retail industry focusing on the principles of justice, social responsibility, and economic balance. The results of the study show that the application of Islamic business ethics in the franchise expansion of the retail industry can improve business performance, strengthen consumer trust, and promote business sustainability. This research highlights the importance of understanding and applying Islamic business ethics principles in the context of modern business, especially in the retail industry.